MAINTAINING THE VALUE OF THAI ARTS AND CULTURE BASED ON BUDDHISM - (Chupradits), Phrakru Sophonthamwisit; (Rakcharoen), Phrakru Pariyatkunawut; Uttamo (Suwannachan), Phrakruvinaithorn Chawalit (Journal of MCU Nakhondhat, 2024)
Cultural capital is intellectual property accumulated in the past. It is valuable to humans and the needs of society. In addition to providing economic value, it is capital used to produce goods and services that have cultural meaning. which is financial capital Service capital in capitalism Today's world is connected to an industry that carries cultural connotations called Product industry A culture that produces cultural goods and services that has culture embedded in the goods and services. Culture helps create order in society. It determines the behavior patterns of members of society. Including creating a pattern of thoughts, beliefs, and values of members in the same format. Helps create unity. A society that has the same culture will have a feeling of connection. Solidarity arose. Dedicated to society Culture determines the shape of the family institution. It is a symbol of national identity. A nation with a high culture It would be praised and a guarantee of national security. Help the country progress If any society has a good and appropriate culture, such as discipline, diligence, patience, and seeing the common good more than the individual. Society will be able to progress. Therefore, the value of preserving Buddhist arts and culture in Thai society today must be preserved. Taking into account the participation of the community in maintaining and developing the arts of the temple. Art in Buddhism is usually created in temples. This is because the temple is the center of Buddhism. Conveying art and Dharma Invite to enter the temple It is a vehicle for perception and understanding of Dhamma principles. Have a mind of merit, be charitable, sacrifice, make donations. Buddhist arts produce results that are of mental value. For those interested in arts and culture